Humble Leadership and Employee Resilience: Exploring the Mediating Mechanism of Work-Related Promotion Focus and Perceived Insider Identity - Zhu, Yanhan; Zhang, Shuwei; Shen, Yimo (Frontiers in Psychology, 2019)
Although the topic of employee resilience has recently received increased attention, existing research has largely failed to explore its situational triggers. Drawing on social information processing theory, the current study integrates the literature of humility and resilience to theorize the underlying mechanism through which humble leadership facilitates employee resilience. This research proposes a potential heterogeneous effect that humble leadership catalyzes employee resilience through multiple pathways. Field (N = 434) and experimental studies (N = 104) conducted in Mainland China support hypotheses that humble leadership enhances employee resilience through simultaneous increases in work-related promotion focus and perceived insider identity. Research implications are discussed, and directions for future research are offered.